STUDENTS’ COVARIATIONAL REASONING REVIEWED FROM COGNITIVE STYLES - Agus Jaenudin (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Covariational reasoning is important for students because it is a basic ability to master mathematical concepts. However, in reality many students have difficulty in working on covariational reasoning. One of the factors that influence covariational reasoning is cognitive style. Therefore, it is necessary to analyze covariational reasoning based on cognitive style. The research method used in this study is a qualitative research on prospective mathematics teacher students as many as 4 people taken from 31 people. The research instrument used in this study was GEFT to determine cognitive style, covariational reasoning worksheets, and interviews. The results showed that subjects with FIK and FIL cognitive styles only met MA 3, but FIL had erroneous thoughts. Meanwhile, FDK only met MA 2 and FDL met MA 1. In general, subjects with FI cognitive style had better covariational reasoning abilities than subjects with FD cognitive style.